Analysis of Metacognitive Approach to The Mathematics Reasoning Ability of Students of State Elementary School of Pamulang 01 - Muhammad Hayun; Nia Kurniawati (EduBasic Journal: Jurnal Pendidikan Dasar, 2022)
This research was motivated by students' low mathematical reasoning ability in elementary schools and the demands of numeracy literacy through the minimum competency assessment (AKM) program launched by the government, requiring students to improve their reasoning abilities by applying a metacognitive approach. This study aimed to determine the effectiveness of the metacognitive approach in improving students' mathematical reasoning abilities on the material of the spatial structure. The method used in this study was an experimental research method with a quasi-experimental approach, with a sample size of 59 students (31 students in the control class and 28 students in the experimental class), with a pretest-posttest-only control group design. The results obtained from the calculation of the independent sample t-test revealed a t-count of 0.356, less than a t-table of 2.002. It indicates no difference in students' mathematical reasoning ability between the experimental and control classes. Thus, the metacognitive learning approach did not significantly affect the mathematical reasoning ability of students in sixth grade of State Elementary School of Pamulang 01. In other words, it can be said that the metacognitive learning approach for students at State Elementary School of Pamulang 01 was not appropriate for learning mathematics. The results of this study are expected to be useful to related parties who can use it, such as school principals, teachers, parents, students, and further researchers.